Pengaruh Brand Image dan Brand Trust Terhadap Keputusan Pembelian Konsumen di PT. XYZ - Gracia Mariana Priscilla (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This study aims to determine whether or not the influence of brand image and brand trust on purchasing decisions at PT. XYZBrand image and brand trust are factors that can influence consumer purchasing decisions. A good brand image will have a positive impact on the company which will ultimately benefit the company through increased consumer purchases of products or services.This study uses a sample and a population of 100 respondents who are still actively studying at PT. XYZ, using purposive sampling method. The results showed that brand image and brand trust had a positive and significant effect on purchasing decisions.